Reproductive factors and risk of cardiovascular outcomes in women with ST-elevation myocardial infarction - Sina Rouhani; Azam Soleimani; Marjan Jamalian; Masoumeh Sadeghi (BMC, 2024)
Abstract Background There are many sex-specific factors affecting myocardial infarction (MI) outcomes in males and females. This study aimed to evaluate the relationship between reproductive factors and cardiovascular outcomes in women after ST-elevation MI. Method This retrospective cohort study was initiated in 2016-2017 at Chamran Hospital, Isfahan, Iran. One hundred eighty women with a diagnosis of ST-elevation MI were followed up for 3 years, and any occurrence of cardiovascular events (CVs) was recorded. All information regarding reproductive factors was recorded via questionnaire. This information was compared between women with cardiovascular events and women without adverse events using a sample t test, chi-square test, and multiple backward logistic regression analysis. SPSS version 24 was used to conduct all analyses. Result Sixty-four women with a mean age of 65.81 ± 13.14 years experienced CV events, and 116 women with a mean age of 65.51 ± 10.88 years did not experience CV events. A history of ischemic heart disease and diabetes mellitus were more prevalent in women with CV events (P = 0.024 and P = 0.019). After adjusting for ischemic heart disease and diabetes mellitus, oral contraceptive pill (OCP) usage was more prevalent in women with CV events than in women without CV events (60.9% vs. 40.4%, P = 0.008). There was a greater chance of CV events in women with OCP usage (OR = 3.546, P = 0.038) and a lower chance of CV events in women with greater age at menarche (OR = 0.630, P = 0.009) and longer breastfeeding duration (OR = 0.798, P = 0.041) according to multiple backward logistic regression models. Conclusion Based on this study, OCP consumption is a risk factor, while older age at menarche and longer duration of breastfeeding are protective factors for cardiovascular outcomes in women after STEMI.